Korelasi Antara latar Belakang Pendidikan dan Ketaatan Beribadah Salat Mahasiswa PAI FTK UIN Ar-Raniry: Latar Belakang Pendidikan, Salat Berjamaah - Zakiatur Rahmi; Safrina Ariani; Alda Risma (IAIN Ambon, 2026)
This study was motivated by differences in educational backgrounds among students in the Islamic Religious Education (PAI) program at UIN Ar-Raniry, which are suspected to influence the level of religious observance, particularly in the practice of congregational prayer. Educational background is often viewed as a key factor shaping an individual’s religious understanding, attitudes, and awareness; thus, it is of scientific interest to examine its relationship with the practice of religious observance. The research question in this study is whether there is a correlation between the educational background of students in the PAI program at UIN Ar-Raniry and their level of observance in congregational prayer. This study aims to determine whether or not there is a relationship between these two variables. The research method used is a quantitative approach with a correlational study design. The study population comprised all students who met the research criteria, while the sampling technique employed purposive sampling, involving a total of 38 respondents. Data collection was conducted via a questionnaire designed based on indicators of adherence to congregational prayer. The collected data were then analyzed using the Chi-Square test with the aid of SPSS software. Based on the results of the Chi-Square test, a Pearson Chi-Square value was obtained using SPSS software. The results of the Chi-Square analysis showed a Pearson Chi-Square value of 11.660, with df = 8 and Asymp. and an asymmetry significance value of 0.167, which is higher than the significance level of 0.05. These findings indicate that there is no significant relationship between educational background and adherence to congregational prayer. Based on these results, it can be concluded that differences in the educational backgrounds of students in the Islamic Education Study Program at UIN Ar-Raniry are not significantly related to the level of adherence to congregational prayer. This finding highlights the need for further research into other factors that influence adherence to religious practices.